Virtual Lab Integrated Flipped Class for Effective Implementation of CDIO Framework in a Theory Course – A Case Study - Kavitha, D.; Anitha, D. (Journal of Engineering Education Transformations, 2025)
CDIO (Conceiving — Designing — Implementing — Operating) Initiative collaborators have adopted CDIO as the framework of their curricular planning and outcome-based assessment which demands more active learning strategies. A flipped classroom is a student centric instructional strategy and a type of blended learning, which aims to increase student engagement and learning by having complete readings at home and work on live problem-solving during class time. Virtual labs are interactive, digital simulations of activities to learn/explain certain concept that improves the content delivery of all types of courses and is helpful for students understanding and applying the concepts in a better way. How can a virtual lab help in flipped mode especially in what type of course? The experiment is conducted for the course 18EE340 -Digital Systems with two sets of students: experimental group with virtual lab integrated Flipped model and controlled group with flipped model without virtual lab. The outcome of the activity is measured using focus group discussions and it is understood that students have involved in the activity with attentiveness and the positive outcome is also seen in the results of CAT performance. It is found that 14.5% improvement is obtained in the experimental group when compared to the controlled group. Also the research study shows that the CDIO skills get improved by adopting the proposed method. On the other hand, this paper also discusses the common errors made in Flipped Class during planning and how to overcome them based on experiential learning using 5 different case studies.